Efektivitas Efektivitas Pelaksanaan Apel Dalam Membentuk Karakter Disiplin Siswa Kelas XII di SMK Al Hadi Gresik - Moh. Irfan Sulthoni Moh. Irfan Sulthoni; Muhammad Ariesdy Prawiranegara Muhammad Ariesdy Prawiranegara; M Nizar Ibnu Zuhri M Nizar Ibnu Zuhri (STAI Terpadu Yogyakarta, 2023)
This study aims to determine the effectiveness of implementing apples in shaping the disciplinary character of class XII students at Al Hadi Gresik Vocational School. The method used is descriptive method with a quantitative approach.Â The sample used amounted to 18 people. Data collection techniques in this study used pretest and posttest and questionnaires with a Likert scale. Data analysis techniques used the Paired T test. The results of the study showed that the results of the analysis between morning apples and the paired T test on the SPSS computer program on student discipline were effective with Sig. 0.00 < 0.05, means that Ho is rejected and Ha is accepted due to the effectiveness of the implementation of the morning assembly in shaping the disciplinary character of students. Furthermore, based on the questionnaire from the responses of Class XII students of Al Hadi Gresik Vocational High School, it shows that the implementation of the morning assembly before learning is quite effective in instilling some good character values such as discipline, responsibility, courtesy and nationalism as well as mutual respect for fellow students and respect for others teacher.